2014
DOI: 10.25011/cim.v37i1.20863
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine improves oxazolone-induced colitis by inhibiting the NF-κB pathway

Abstract: Tetramethylpyrazine improves oxazolone-induced colitis by inhibiting the NF-κB pathway Abstract Purpose: Tetramethylpyrazine (TMP) is an e ective Chinese plant-derived medicine for colitis in the clinic, but the underlying molecular mechanisms of its use remain poorly understood. e purpose of this study was to investigate the mechanisms involved in its therapeutic action.Methods: A colitis mouse model was induced by oxazolone enema. TMP was administered at 80 mg/kg/day and sulphasalazine (SASP) was used as pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In vitro assays have demonstrated that tetramethylpyrazine significantly inhibits NF-kB translocation via IkB-a-dependent reduction of pro-inflammatory cytokines, such as TNF-a, IL-6, and IL-8, and the generation of damaging compounds, such as ROS (Scirpo et al, 2015). In addition, the same studies in OXAinduced colitis mice indicated that treatment with Tetramethylpyrazine could improve the outcome of intestinal inflammation via PPARg signaling-mediated inhibition of NF-kB signaling (Lu et al, 2014).…”
Section: Role For Pparg As a Modulator Of Cytokine/chemokine Productionmentioning
confidence: 95%
“…In vitro assays have demonstrated that tetramethylpyrazine significantly inhibits NF-kB translocation via IkB-a-dependent reduction of pro-inflammatory cytokines, such as TNF-a, IL-6, and IL-8, and the generation of damaging compounds, such as ROS (Scirpo et al, 2015). In addition, the same studies in OXAinduced colitis mice indicated that treatment with Tetramethylpyrazine could improve the outcome of intestinal inflammation via PPARg signaling-mediated inhibition of NF-kB signaling (Lu et al, 2014).…”
Section: Role For Pparg As a Modulator Of Cytokine/chemokine Productionmentioning
confidence: 95%
“…At intestinal level, for example, under pathological conditions, an enhancement of iNOS expression leads to an over production of nitric oxide (NO). This condition determines a loss of barrier function with epithelial disruption and bacterial translocation, which triggers the inflammation [133,134]. NO has in fact been recognized as involved in the etiology of this kind of mucosal inflammation such as Crohn's disease and ulcerative colitis [135].…”
Section: Inos Modulationmentioning
confidence: 99%
“…As inhibition of PPAR-γ signaling would lower the beneficial effect of tetramethylpyrazine, it is suggested that the effect of tetramethylpyrazine treatment in colitis is independent of PPAR-γ. In vitro assays also demonstrated that tetramethylpyrazine (40 μg/mL) could significantly inhibit NF-κB translocation, which reduces the production of inflammatory factors TNF-α, IL-6, IL-8, and ROS in LPS treated Caco-2 cells (Lu et al, 2014). These results indicated that tetramethylpyrazine could ameliorate intestinal inflammation by activating the PPAR-γ signaling pathway and inhibiting the NF-κB p65 signaling pathway.…”
Section: Plant-based Alkaloids Against Ibdmentioning
confidence: 99%